Innovative Contextual Learning Model Based on Bugis Local Wisdom to Enhance Cultural Literacy of Junior High School Students - Muhammad Tahir; Ventje Jany Kalukar; Yasysyar Hidayat (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
This study explores the integration of Bugis local wisdom into an innovative contextual learning model to enhance cultural literacy among junior high school students. Using a qualitative research approach through a systematic literature review, the study analyzes existing academic literature related to contextual learning, local wisdom in education, and cultural literacy. The findings reveal that contextual learning, when coupled with local wisdom, significantly improves student engagement and academic performance by making learning more relevant and connected to students’ cultural identities. The incorporation of Bugis cultural values and traditions, such as mutual respect and cooperation, not only strengthens students’ understanding of their heritage but also fosters a sense of pride and belonging. However, challenges such as the lack of adequate teaching materials and insufficient teacher training were identified as barriers to effective implementation. Despite these challenges, the study highlights the potential of this approach to serve as a model for other multicultural societies, advocating for a curriculum that balances global education standards with local cultural content. This research contributes to the growing body of literature on culturally responsive teaching and provides insights into how local wisdom can be integrated into educational systems to foster cultural literacy. The study recommends further empirical research to test the effectiveness of this model in real classroom settings and to explore its applicability in other ethnic contexts.